Pemanfaatan Tanaman Sela pada Lahan Budidaya Jambu Kristal (Psidium guajava L.) di Desa Neglasari - Muhammad Izzul Fikri Noor; Yannefri Bakhtiar; Amiruddin Saleh (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
West Java is the second-largest producer of guava (Psidium guajava L.) in Indonesia. One of the cultivars that are quite popular with the community is the guava crystal. Farmers in Neglasari Village have begun to cultivate guava crystals with alley croping cultivation techniques. This study aims to determine the effectiveness of the use of alley croping in the cultivation of guava (Psidium guajava L.) in Neglasari Village. The method used in this activity is interviews, field observations, and literature review. Interviews were conducted directly with farmers while observing on cultivated land. Information from interviews is strengthened by conducting a literature review of sources relevant to the topic. Utilization of intercrops has the advantage of providing additional income for farmers, especially during the immature period, reducing the level of land erosion, increasing the availability of nutrients in the soil, and helping control pests and diseases in plants. Keywords: Alley cropping, crystal guava, cultivation techniques